Examining the Relationship of Keyword Analysis using Online Traveller Hotel Reviews - Zuraini Zainol; SH Lee, Angela; NE Nohuddin, Puteri; Ibrahim, Noor Farizah; Ahmad Hijazi, Mohd Hanafi (International Journal on Perceptive and Cognitive Computing, 2022)
With a large number of reviews being posted daily, online travel forums have become a very common platform for sharing travel information. Travel websites including TripAdvisor.com and Booking.com have become invaluable tools for hoteliers and travellers alike, enabling them to advertise hotel rooms, select hotels, and solicit and exchange reviews. This research paper uses data collected from TripAdvisor websites and 5501 reviews were collected from 4 different four-star hotels in Kuala Lumpur from 2012-2017. The work aims to extract the keyword (factors) that influence travellers in their choice of hotels using the framework of Visualizing Keyword Relationship Analysis (VKRA). The relationships of these keywords are illustrated using text analytics visualization techniques which are term frequency, keyword association and keyword network graph. The incorporation of these text analytics techniques offers insights for (i) travellers to view the opinions of other travellers on these hotels and (ii) hoteliers to understand travellers’ preferences (location, room, services) and experiences, and improve their services in the future.